European Competition Law in the face of «sustainability agreements» - de la Vega García, Fernando (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
This paper studies the inclusion of sustainability as a European criterion in the antitrust evaluation of undertaking agreements, analyzing the various actions that confirm the relevance of Competition Law for the ecological transition. Among them, the incidence of the Sustainable Development Goals (SDGs) stands out, especially those related to the environment, in the authorization of vertical agreements and conduct related to the agricultural market, as well as in the public application of Competition Law. The paper also examines the inclusion of sustainability agreements in the Draft of «Guidelines on the applicability of article 101 of the Treaty on the Functioning of the European Union to horizontal co-operation agreements» (2022).
Keywords: competition; sustainability; «Green Deal»